2018
DOI: 10.1111/ele.13090
|View full text |Cite
|
Sign up to set email alerts
|

Species composition, functional and phylogenetic distances correlate with success of invasiveChromolaena odoratain an experimental test

Abstract: Biotic resistance may influence invasion success; however, the relative roles of species richness, functional or phylogenetic distance in predicting invasion success are not fully understood. We used biomass fraction of Chromolaena odorata, an invasive species in tropical and subtropical areas, as a measure of 'invasion success' in a series of artificial communities varying in species richness. Communities were constructed using species from Mexico (native range) or China (non-native range). We found strong ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 74 publications
1
42
0
1
Order By: Relevance
“…The relationship between a community's functional diversity and its invasibility has been studied mainly through small‐scale experimental treatments of plant communities, where more functionally diverse communities inhibit the establishment and growth of alien species (Dukes , Maron and Marler , Zheng et al. ). Our large‐scale observational study results contradict these findings, since high native functional diversity was positively associated with alien species richness.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between a community's functional diversity and its invasibility has been studied mainly through small‐scale experimental treatments of plant communities, where more functionally diverse communities inhibit the establishment and growth of alien species (Dukes , Maron and Marler , Zheng et al. ). Our large‐scale observational study results contradict these findings, since high native functional diversity was positively associated with alien species richness.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, our third hypothesis, late-successional forest soils exhibit stronger allelopathic inhibition to P. americana than early successional soils, was not supported. Thus, differences in the species composition of communities, which leads to species-specific allelopathic effects on invasive species, may be a more promising explanation [8,25,66] than succession.…”
Section: The Effects Of Allelopathy On Plant Growthmentioning
confidence: 99%
“…Understanding the factors that regulate community invasibility is critical for predicting and controlling plant invasions [3]. Prior studies have shown that successful plant invasions are related to the vegetation characteristics of recipient communities; these characteristics actually affect both the resource availability of habitats and biotic resistance [4][5][6][7][8]. For example, high species diversity sufficiently fills available niches and limits resource supply for invaders, while native species decrease establishment success of invader species that are similar to them in species traits (limiting similarity) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present new analyses of our previous experimental data (Zheng et al, 2018), incorporating evolutionary models. In a common garden experiment manipulating the composition of resident plant communities, we (Zheng et al, 2018) found that communities with functionally distant close relatives had the greatest invader biomass. This runs counter to the classic assumption that close relatives should be functionally similar (Darwin, 1859).…”
Section: A Case Study Invasion Experimentsmentioning
confidence: 99%
“…Root traits might be Fig. 1 The relationship between phylogenetic and functional distance in an experiment with the invader Chromolaena odorata (Zheng et al, 2018). Distances are calculated from the invader, Chromolaena odorata, for resident species from the native range in Mexico (blue triangles) and the introduced range in China (red circles) (see Supporting Information Notes S1 for Newick formatted phylogeny).…”
Section: Key Evolutionary Implicationsmentioning
confidence: 99%